The Values of Islamic Religious Education in the Hajat Bumi Tradition in Sindangsari Village, Karawang - Awwaliya Nurrohmah; Aulia Fitria; Azizah Ramadhani; Candra Indra Prahasta; Fanya Azzahro (Penerbit Hellow Pustaka, 2025)
The Hajat Bumi tradition is one of the agrarian cultural heritages that is still preserved by rural communities in West Java, particularly in Sindangsari Village, Kutawaluya District, Karawang Regency. This tradition not only serves as a traditional ceremony to express gratitude to God for the fruits of the earth, but also as a means of strengthening social relations and reinforcing the values of community togetherness. This study aims to examine the Islamic, social, and cultural values contained in the implementation of Hajat Bumi and its relevance to modern society. The method used is a literature study by examining various sources. The results of the study show that the Hajat Bumi tradition contains values of mutual cooperation, social solidarity, tolerance, and equality that strengthen social cohesion within the community. In addition, Hajat Bumi also serves as an educational tool in instilling moral values, social responsibility, and respect for nature and ancestral heritage. These values are in line with Islamic teachings on ukhuwah (brotherhood), gratitude, charity, and caring for others. Thus, the Hajat Bumi tradition not only has ritual and cultural significance, but also plays an important role as a medium for preserving social, cultural, and religious values that are relevant to the lives of today's society.